Establishment of the confinement loss curve using the tunnel convergence data. (2nd October 2020) - Lee, Yu-Lin
ABSTRACT: The confinement loss plays an important role that connects two two-dimensional planes, cross-section, and longitudinal section. In the analysis of cross-section, the two-dimensional plane–strain condition takes into account the behavior of ground–support interaction and the confinement loss is applied to simulate the variation of internal support pressure due to the effect of advancing excavation of tunnel face. In the third direction (longitudinal section), this tunnel advancing effect can be investigated by establishing the confinement loss curve (CLC) and considering the mathematical hyperbolic function proposed in this study. The arrangement procedure for the tunnel convergence data is proposed to use the coordinate translation method to match this regression function. In addition, the functions estimating the values of confinement loss at the unsupported span and at the tunnel face are also suggested. According to the results obtained, the confinement loss is a variable independent of initial stress and location of measurement, and obviously, it's dependent on the physical property of the geological material in question and the unsupported span of the tunnel. This estimation method can be applied to obtain the confinement loss for the calculation of support pressure and pre-convergence of the tunnel in the numerical simulation and the theoretical analysis.